Chronic exposure to MK-801 leads to olfactory deficits and reduced neurogenesis in the olfactory bulbs of adult male mice - Sinegubov, Artem; Dyachuk, Vyacheslav (Frontiers in Behavioral Neuroscience, 2024)
In this manuscript, we describe a series of experiments aimed at elucidating the role of olfaction in the impairment of social behavior in mice after administration of NMDA receptor antagonists. We believe that it can be published in Frontiers, because the topic of the manuscript, primarily considering the relationships between neurogenesis and behavior of model animals, fits the scope of the journal. We suggest that the Pathological Conditions section is most suitable for this, as our study is closely related to the problem of modeling schizophrenia in animals.